Please answer the question in attachment
Attachments:
![](https://hi-static.z-dn.net/files/de8/f08e413f70c4480951d1bdaea16f25b3.png)
Answers
Answered by
2
Answer:
u write wrong p(x)
ax² not a²
hope I'm right
follow me on brainly
also on Instagram I'd
skg9304
Attachments:
![](https://hi-static.z-dn.net/files/d40/97245c8d9c7c70bbd57b75d94c6b37e8.jpg)
Answered by
1
from remainder theorem, when p(x) is divided by x - a, the remainder is p(a)
p(x) = x^3. - a^2 + 6x - a
remainder = p(a)
p(a) = a^3 - a^2 + 6a - a
= a^3 - a^2 + 5a
[ note : from symmetry, it seems that the p(x) may be
p(x) = x^3 - ax^2 + 6x - a
in that case, remainder would be
p(a) = a^3 - a*a^2 + 6a - a
= a^3 - a^3 + 5a
= 5a
]
Similar questions